Hubungan Antara Perawatan Diri Dengan Body Image Pada Mahasiswa Keperawatan Stikes Mahardika Cirebon - Sumarni; Ananda Yusuf, Andinna; Fibriyani, Risma (Awatara Publisher, 2024)
Self-care is carried out to maintain health, both physically and psychologically. The purpose of this study is to find out how the relationship between self-care and body image in STIKes Mahardika Cirebon nursing students. every person who does self-care starts from the physical appearance he has giving an image or perception of body shape, then moving on to the physical appearance that belongs to others this is what is called body image. This research method uses descriptive correlation using a cross sectional approach. The sample of this study was in STIKes mahardika nursing students totaling 154 respondents using Accidental sampling techniques. The instruments used are questionnaires . The results of the study were obtained sufficient self-care (55.8%), and negative body image (43.5%). After the statistical test, a p value of 0.004 ≤ 0.05 was obtained, which means that there is a significant relationship between self-care and body image in STIKes Mahardika Cirebon nursing students